2018
DOI: 10.3389/fped.2018.00201
|View full text |Cite
|
Sign up to set email alerts
|

Cantrell Syndrome—A Rare Complex Congenital Anomaly: A Case Report and Literature Review

Abstract: Cantrell syndrome (CS) or pentalogy of Cantrell is defined as a rare condition involving a midline anterior abdominal wall defect, a distal sternal cleft, a defect of the anterior diaphragm, and a defect of the apical pericardium with pericardio-peritoneal communication, as well as intracardiac anomalies. We report the case of a male newborn with type 2 CS diagnosed during intrauterine life based on ultrasonographic evaluation. Clinical examination at birth revealed an abdominal wall defect with extrathoracic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0
7

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 22 publications
1
15
0
7
Order By: Relevance
“…It has also been called Cantrell syndrome or deformity, thoraco-abdominal syndrome, and X-linked midline defect. The incidence of occurrence is estimated in the literature to be from 1 in 65,000 to 1 in 200,000 live births [2,3,4].…”
Section: Discussionmentioning
confidence: 99%
“…It has also been called Cantrell syndrome or deformity, thoraco-abdominal syndrome, and X-linked midline defect. The incidence of occurrence is estimated in the literature to be from 1 in 65,000 to 1 in 200,000 live births [2,3,4].…”
Section: Discussionmentioning
confidence: 99%
“…Cantrell’s syndrome or pentalogy have been well described in humans, with an estimated prevalence between 1:65 000 and 1:200 000,2 whereas, to the authors’ knowledge, an incomplete form of the syndrome has been reported in dogs and cats rarely3–10; a complete pentalogy has only been reported in one litter of puppies 11. Therefore, the true prevalence in animals is unknown due to the rare nature of this syndrome.…”
Section: Discussionmentioning
confidence: 88%
“…The prognosis for human patients with Cantrell’s pentalogy depends mainly on the severity and complexity of the cardiac anomalies and despite considerable advances in the management of this syndrome, survival rates are fairly low 2 14 16 17…”
Section: Discussionmentioning
confidence: 99%
“…The incidence is reported increased with the presence of trisomy 13 and 18 [20,21]. Mutation in the Porcupine homolog gene was reported in a patient with PC and focal dermal hypoplasia and in those with the limb-body wall complex syndrome [22,23] Porcupine, an O-acyltransferase involved in the acylation of Wnt ligands, is located on the X chromosome, and its deletion in mice is known to cause focal dermal hypoplasia and developmental anomalies of it's body wall [24] However, it is unclear if a mutation in Porcupine also causes PC [25]. Most cases so far were described sporadic, but in some families, an X-linked pathway has been suggested and in some cases alterations in the region, Xq25-q26.1 had been found [7].…”
Section: Discussionmentioning
confidence: 99%
“…Prenatal imaging studies are crucial for prenatal counseling and adequate postnatal therapeutic planning [25]. The diagnosis of PC may be established by fetal ultrasonography during the first trimester of the pregnancy as early as 10 weeks of pregnancy [26,27].…”
Section: Discussionmentioning
confidence: 99%